2021
DOI: 10.1155/2021/9961308
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Knowledge, Attitude, and Practices among School Teachers in Chitwan District, Nepal

Abstract: Background. Oral health is dependent on the knowledge and awareness of the individuals. Teachers as individuals influence the children in every aspect including oral health maintenance. The objective of this study was to assess the oral health knowledge, attitude, practices, and oral health status among school teachers in Chitwan District, Nepal. Materials and Methods. A cross-sectional study was conducted on 550 school teachers of private and government schools in Chitwan District, to assess the knowledge, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
4
2
1
Order By: Relevance
“…In the present study, an equal number of subjects believed that gum disease affects overall health attitude and majority agreed that early diagnosis and treatment of gum disease reduces its severity and that following dentist's instructions can avoid gum diseases. The findings are in accordance with a study done by Singh et al where the majority knew that the health of the mouth impacts the health of the body and that dental treatment is important as any other treatment [15]. The vast majority of the subjects thought that cavities and gum diseases are caused by infections in the oral cavity which is contradictory to a study by Azodo C et al, who reported very few subjects attested that plaque or infections in the mouth can result in periodontal disease and dental caries [12].…”
Section: Response To Practice Questionssupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, an equal number of subjects believed that gum disease affects overall health attitude and majority agreed that early diagnosis and treatment of gum disease reduces its severity and that following dentist's instructions can avoid gum diseases. The findings are in accordance with a study done by Singh et al where the majority knew that the health of the mouth impacts the health of the body and that dental treatment is important as any other treatment [15]. The vast majority of the subjects thought that cavities and gum diseases are caused by infections in the oral cavity which is contradictory to a study by Azodo C et al, who reported very few subjects attested that plaque or infections in the mouth can result in periodontal disease and dental caries [12].…”
Section: Response To Practice Questionssupporting
confidence: 92%
“…A majority of the subjects were not aware about their bleeding gums or presence of gum disease. This is in contrast with the findings by Manjunath et al and Singh et al where a greater proportion of the school teachers think gum bleeding means inflamed gums [15,16]. Very few subjects complained of tooth mobility but the majority of the subjects agreed that gum diseases if not treated, can progressively cause tooth loss.…”
Section: Response To Practice Questionscontrasting
confidence: 73%
“…This information can validate the present study in which the teachers did not show any significant statistical difference regarding knowledge of oral health irrespective of their educational qualification. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Hal ini sejalan dengan penelitian oleh Baltaci et al 12 yang menyatakan bahwa 83% guru setuju bahwa kunjungan rutin ke dokter gigi efektif untuk pencegahan karies. Singh et al 13 menyatakan bahwa di antara guru sekolah swasta di Chitwan District, Nepal, sebanyak 200 guru (72,7%) memiliki sikap kesehatan gigi dan mulut yang baik. Demikian pula, di antara guru sekolah pedesaan, sebanyak 215 guru (78,2%) memiliki sikap kesehatan gigi dan mulut yang baik.…”
Section: Bahasanunclassified